Analisis Pengaruh Profitabilitas, Solvabilitas, Ukuran Perusahaan Dan Ukuran Kap Terhadap Audit Delay - Ifita Meidina; Nilda Tartilla (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This research aims to determine: (1) The effect of profitability on audit delay in manufacturing company sector consumer goods industry which is listed on the Indonesia Stock Exchange (IDX) in 2016-2019. (2) The effect of solvability on audit delay in manufacturing company sector consumer goods industry which is listed on the Indonesia Stock Exchange (IDX) in 2016-2019. (3) The effect of the firm size on audit delay in manufacturing company sector consumer goods industry which is listed on the Indonesia Stock Exchange (IDX) in 2016-2019.(4) The effect of public accounting’s size on audit delay in manufacturing company sector consumer goods industry which is listed on the Indonesia Stock Exchange (IDX) in 2016-2019. (5) The effect of profitability, solvability, firm size, and public accounting’s size on audit delay in manufacturing company sector consumer goods industry which are listed on the Indonesia Stock Exchange (IDX) in 2016-2019. The samples in this research were 21 companies selected based on purposive sampling technique. With purposive sampling technique, 21 companies are acquired as a sample with 4 years of observation period, so the total samples of this research is 84 samples. Analysis method used are descriptive statistics, the assumptions of classical test, and multiple regression analysis. The results of this research show that profitability, solvability, and public accounting’s size have a significant effect on audit delay, while the firm size has no effect on audit delay. Profitability, solvability, firm size, public accounting’s size simultaneously effect on audit delay. Key words : Profitability, Solvability, Firm Size, Public Accounting’s Size, Audit Delay